Etika Bisnis dalam Ekonomi Digital: Studi Kasus Penerapan Prinsip Kejujuran pada Platform E-Commerce UMKM di Indonesia - Jati Imantoro (Pusat Riset dan Inovasi Nasional, 2025)
The digital transformation has significantly reshaped marketing strategies, especially for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. In digital marketing contexts, honesty emerges as a crucial ethical concern, as business actors face temptations to manipulate information for immediate gains. This study aims to explore the practice of honesty in digital marketing among MSMEs and examine the role of Islamic business ethics in shaping ethical behavior. Employing a qualitative case study approach, in-depth interviews were conducted with MSME actors actively utilizing digital platforms for product promotion. Findings reveal that honesty in conveying product information is a key factor in building consumer trust, and MSMEs internalizing Islamic ethical values demonstrate greater consistency in practicing honest marketing. This research offers significant implications for developing sustainable, value-based MSME business models and provides strategic input for policymakers to design contextual digital business ethics regulations and training programs.